LEGAL RESPONSIBILITY FOR UNHYGIENIC PRACTICES AT SEC BOWL RESTAURANT - Anshari, Abu Thalhah Al; Ratrisasi, Elizabeth Prima; Dewani, Maheswari Queena; Januarita, Shintia; Atmadja, Wilhelmina Setia (Sekolah Tinggi Ilmu Hukum Awang Long, 2025)
One of the restaurants that announced the permanent closure of its restaurant branch in Kuningan Jakarta is the Sec Bowl restaurant. The Sec Bowl restaurant is allegedly permanently closed because of a video influencer named Codeblu. Real name William Anderson, he is known as a restaurant and food reviewer who has 14 million followers on TikTok. The content he often uploads is criticism or praise in the form of photos or videos of the food he has tried. Codeblu made a reaction video to a photo sent to him, which showed the condition of the toilet at Sec Bowl. In his video, the influencer said that the place was